2015
DOI: 10.1002/ejhf.218
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of MinerAlocorticoid Receptor antagonist Tolerability Study‐Heart Failure (ARTS‐HF): a randomized study of finerenone vs. eplerenone in patients who have worsening chronic heart failure with diabetes and/or chronic kidney disease

Abstract: Aims To investigate the safety and potential efficacy of the novel non‐steroidal mineralocorticoid receptor antagonist finerenone in patients with worsening chronic heart failure and reduced left ventricular ejection fraction (HFrEF) and at high risk of hyperkalaemia and worsening renal dysfunction. Methods and results The MinerAlocorticoid Receptor antagonist Tolerability Study‐Heart Failure (ARTS‐HF; NCT01807221) is a multicentre, randomized, double‐blind, active‐comparator‐controlled, six‐parallel‐group, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 43 publications
0
54
0
5
Order By: Relevance
“…The design of ARTS-HF Japan is based on the design of the international ARTS-HF, 17 and was a randomized, doubleblind, active-comparator-controlled, parallel-group, phase 2b, dose-finding study conducted at 31 centers in Japan. The study protocol was developed by the sponsor (Bayer Yakuhin Ltd), and was approved by independent ethics committees and/or institutional review boards for all participating centers before the study began.…”
Section: Methodsmentioning
confidence: 99%
“…The design of ARTS-HF Japan is based on the design of the international ARTS-HF, 17 and was a randomized, doubleblind, active-comparator-controlled, parallel-group, phase 2b, dose-finding study conducted at 31 centers in Japan. The study protocol was developed by the sponsor (Bayer Yakuhin Ltd), and was approved by independent ethics committees and/or institutional review boards for all participating centers before the study began.…”
Section: Methodsmentioning
confidence: 99%
“…The authors then discuss finerenone the nonsteroidal mineralocorticoid receptor antagonist that has superior cardiac selectivity as compared to spironolactone and eplerenone. The ARTS study [14] confirmed the association of finerenone with a lower increase in serum potassium compared to spironolactone in patients with mild to moderate chronic kidney disease. The subsequently completed larger ARTS-HF trial in patients with diabetes and or mild to moderate kidney disease that compared finerenone to eplerenone showed promising results that included reduction of all secondary end points including CV hospitalization, CV death and total mortality.…”
Section: Potential New Drugsmentioning
confidence: 68%
“…No significant differences were found in the main objective (30% decrease of NT-proBNP levels), or in safety (same incidence of potassium .5.6 mEq/L with both drugs, 4.3%). 69 An improvement was observed in most of the secondary objectives (cardiovascular hospitalization, cardiovascular mortality, and mortality for any other reason; hazard ratio [HR] 0.56; P=0.0229), mainly in subgroups that received higher doses of finerenone (7.5 and 10 mg). For this reason, a new clinical trial has been designed (BAY 94-8862) 70 to evaluate the morbimortality as main objective in a similar population (diabetics or patients with stage III CKD) treated with high doses of finerenone.…”
Section: New Perspectives In Prevention and Treatment Of Hyperkalemiamentioning
confidence: 99%